Determinan Profitabilitas dengan Leverage sebagai Pemoderasi - Wijaya, Temi Adi; Pardede, Tiolina Evi Nausta (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of firm size and sales growth on profitability by using leverage as a moderating variable. This research method uses moderated regression analysis with a quantitative approach using SPSS 25 software. The sample selection technique in this study uses a purposive sampling method with 30 companies listed on the Indonesia Stock Exchange for three periods. The results of the study indicate that company size and sales growth have an effect on profitability, leverage can strengthen the effect of company size on profitability but cannot strengthen the effect of sales growth on profitability